2017
DOI: 10.1002/prep.201600168
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Sensitivity Study of Dihydroxyl Ammonium 5,5′‐Bistetrazole‐1,1′‐diolate (TKX‐50)‐based Melt Cast Explosive Formulations

Abstract: Dihydroxyl ammonium 5,5′‐bistetrazole‐1,1′‐diolate (TKX‐50) is a promising energetic material with predicted performance similar to RDX as well as to CL‐20. In the present study, TKX‐50 was evaluated as a possible replacement for RDX in TNT‐based, aluminized as well as non‐aluminized melt cast formulations. Thermal analysis reveals the compatibility of TKX‐50 with benchmark explosives like RDX and TNT in explosive formulations. This paper describes the thermal and sensitivity study of TKX‐50 with RDX and TNT‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The thermal behaviour of TKX-50 and the kinetics of its thermal decomposition were studied using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). It was found that the thermal decomposition [92] of TKX-50 starts in the range 210-250 °C, depending on the heating rate.…”
Section: Imidazole Based Hemsmentioning
confidence: 99%
“…The thermal behaviour of TKX-50 and the kinetics of its thermal decomposition were studied using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). It was found that the thermal decomposition [92] of TKX-50 starts in the range 210-250 °C, depending on the heating rate.…”
Section: Imidazole Based Hemsmentioning
confidence: 99%
“…the bicyclic backbone constructed by 1,2,4-triazole and 1,2,4-oxadiazole presents a perfect planar configuration, which still exists in the crystal structure of its EMSs. The torsion angles of N1−C1−C3−N6 0.7(12)°, N1−C1−C3−N5 −177.7(9)°, and N2−C1−C3− N6 −177.4(8)°indicate that the two five-membered rings are almost on the same plane. The degree of dihedral angle C4− N7−N8−O2 −179.9(8)°indicates that the −NO 2 group is coplanar with its connecting triazole.…”
mentioning
confidence: 94%
“…For example, 5-nitro-1,2,4-triazol-3-one (NTO), as insensitive ammunition with high energy ( D = 6880 m·s –1 ), low vulnerability, and enhanced stability, has been used in a variety of explosive charges (including melt-cast explosives and PBX explosives). Another typical example is dihydroxylammonium 5,5′-bistetrazole-1,1′-diolate (TKX-50). As a new environment-friendly energetic material with excellent detonation velocity ( D = 9698 m·s –1 ), low sensitivity (IS = 20 J), good thermal safety ( T d = 221 °C), and clean gaseous products (N 2 ), TKX-50 is regarded as a potential component in melt-cast explosive formulations and propellants. , Recently, due to environmental pollution, the application of traditional pyrotechnic compositions has been limited, leading to the exploration of the application of nitrogen-rich heterocycle-based materials in the field of pyrotechnics. Many traditional pyrotechnic formulations contain various toxic and harmful substances, such as perchlorate, nitrate, and chlorinated organic materials, which release hazardous and poisonous products in the form of gas or smoke during combustion and deflagration, causing pollution to the environment and affecting human health. Given the environmental restrictions, it is highly desirable to develop novel environmentally friendly pyrotechnic compounds and formulations. As nitrogen-rich heterocyclic compounds possess excellent characteristics, such as high nitrogen content, good safety, and non-toxicity, their energetic metal salts (EMSs) quickly become the main approach to designing and preparing new “green” pyrotechnic compositions and formulations. In contrast to conventional pyrotechnics, these nitrogen-rich heterocyclic EMSs obtain energy from their high heats of formation due to the existence of the nitrogen-rich heterocycles rather than deriving energy from the oxidation process of the carbon backbone. Moreover, the high energy of these compounds, combined with the large amount of N 2 released during their decomposition, can provide a large flame area, bright fireworks, and ideal color performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although TKX-50 reveals outstanding theoretical performances, it has failed to achieve the desired effect in some practical applications [12][13][14]. The particle size of conventionally-manufactured TKX-50 distributes from dozens to hundreds of microns with sharp-edged irregular shapes [15].…”
Section: Introductionmentioning
confidence: 99%